2009
DOI: 10.1016/j.mimet.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasensitive rapid immunocytotoxicity assay for detecting Clostridium difficile toxins

Abstract: We describe a novel ultrasensitive cell-based immunocytotoxicity assay for detecting less then 1 pg/ml of Clostridium difficile toxins in porcine clinical samples. The assay is simple to perform with a turnaround time of approximately 3 hours and capable of detecting less then 1 pg/ml of toxin A. Using this assay, we were able to detect the presence of C. difficile toxins in the fecal and serum specimens of experimentally infected piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…Previously, He et al reported the detection of C. difficile toxins in samples from experimentally infected piglets (8). Unlike the classical cytotoxigenic culture or toxin neutralization assays, The toxin concentration for a specimen is calculated based on the time for a 50% nCI drop after addition of specimen to the cells and the formula y ϭ 4.6715x Ϫ0.5659 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, He et al reported the detection of C. difficile toxins in samples from experimentally infected piglets (8). Unlike the classical cytotoxigenic culture or toxin neutralization assays, The toxin concentration for a specimen is calculated based on the time for a 50% nCI drop after addition of specimen to the cells and the formula y ϭ 4.6715x Ϫ0.5659 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell responses were monitored on the RTCA system for up to 48 h after addition of processed specimen. the RTCA assay is amenable to a high-throughput platform with decreased hands-on time, decreased turnaround time, and objective measures of cytotoxicity as determined by the cell index parameter (8,25). This dimensionless parameter is derived from changes in electrical impedance across the electrodes of the device in response to cellular responses to C. difficile toxins present in clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicity assay We used the ultrasensitive immunocytotoxicity assay developed by our laboratory 10 to measure toxin in serum, body fluids and intestinal contents. Briefly, mRG1-1 cells expressing the FCγR1-α chain were added to wells of a standard 96 well plate, and incubated overnight before use.…”
Section: Methodsmentioning
confidence: 99%
“…9 We chose doses for the two toxins based on our previous measurements of toxins in the serum, as well as the relative cytotoxicity in cell-based assays, the standard for measurement of toxins in samples, which indicate that TcdB is more toxic to cells at lower concentrations than is TcdA. 10 Based on both of these previous results, we administered 10 μg of TcdA and 1 μg of TcdB to piglets via intraperitoneal injection.…”
Section: Systemic Administration Of Tcda and Tcdbmentioning
confidence: 99%
“…This qualitative, subjective assay is approximately 86% sensitive compared to TC (16) and primarily detects toxin B, which is far more potent than toxin A in this assay (18); specificity of cytotoxicity is confirmed by neutralizing antitoxin antibodies. Like TC, this assay is slow (requiring 24 to 48 h of incubation), nonstandardized, and not widely used for clinical testing.…”
Section: Current Diagnostic Strategies and Their Limitationsmentioning
confidence: 97%